Tracking High-Risk, Violent Offenders: An Examination of the National Flagging System - Yessine, Annie K. (Canadian journal of criminology and criminal justice, 2006)
The present study investigated the effectiveness of the Canadian National Flagging System (NFS), a policy initiative intended to identify offenders who are judged to be suitable candidates for a Dangerous Offender (DO) or a Long-Term Offender (LTO) application. Analyses comparing the profiles of 256 flagged offenders and 97 known high-risk, violent offenders indicated that the flagged offenders generally showed less serious and persistent criminality characteristics than the known high-risk, violent offenders. However, scores on actuarial measures of risk demonstrated that both groups comprised especially high-risk offenders. Furthermore, the violent and/or sexual reconviction rates of the flagged offenders were significantly higher than those reported among the typical Canadian male federal offender population. Judged against our expectations, the base rate of DO/LTO designations among the violent/sexual recidivist flagged offenders was also much higher than the one estimated among the general high-risk, violent offender population in Canada. As a whole, the findings suggested that the NFS was successful in appropriately identifying offenders who pose a risk to the community as well as in subsequently responding to this threat by facilitating the use of the DO/LTO provisions. Recommendations for the development of guidelines to assist criminal justice professionals in screening, monitoring, and processing high-risk, persistent offenders are made. (English) [ABSTRACT FROM AUTHOR]